Innovation in the Sphere of Augmented and Virtual Reality Technologies in EU Member States and Other Countries of the World - Davydov Denys S.; Riabovol Dmytro A. (Problemi Ekonomiki, 2019)
Problems and prospects for the application of innovative technologies of augmented and virtual reality (AR / VR) in various business areas are considered. The main trends in and features of the formation of technological and business base for creating products in the field of AR / VR for mass use in production and customer service are highlighted. The key participants in the global market for devices and applications in this sector as well as all options for their using at the present time are listed. The areas of practical application of the existing solutions are shown, the positive and negative factors are revealed. The features of various segments of wearable devices (Microsoft HoloLens) as well as mobile applications (ZapBox) are analyzed. The necessity for further development and implementation of AR technologies against the background of increasing digitalization processes and automation of production processes in the context of Industry 4.0 is justified.